The Collisium (Raton Range Raton, NM, 1978)
Article is about entertainment facilities in Raton in the early years. The Collisium, was built in 1906 by Mr. Hugo Seaburg, it was located on Third Street and burned in 1914. Talks about the first opera house in what is now the New York and Golden Rule Store. The two story building was erected in 1882 by a Mr. Furgeson and Timothy F. McAuliffe, father of Mrs. Earl T. (Addie) Smith. The opera house occupied the second story while a mercantile business was operated below.
Newspaper article + Photograph of the inside of the Collisium.
Master list item #: 96
File location is in the Raton file Cabinet
Keywords: Seaburg, Hugo; Furgeson, Mr; McAuliffe, Timothy F; Smith, Addie McAuliffe; Collisium -- 1906-1914; Apollo Laundromat; New York and Golden Rule Store; Business History; Local Business; Entertainment; Opera Houses; Theators; Third Street -- Raton, New Mexico; First Street -- Raton, New Mexico